2018
DOI: 10.1002/cpp.2299
|View full text |Cite
|
Sign up to set email alerts
|

Brief coping strategy enhancement for distressing voices: Predictors of engagement and outcome in routine clinical practice

Abstract: Cognitive behaviour therapy is recommended internationally as a treatment for psychosis (targeting symptoms such as auditory hallucinations, or "voices"). Yet mental health services are commonly unable to offer such resource-intensive psychological interventions. Brief, symptom-specific and less resource-intensive therapies are being developed as one initiative to increase access. However, as access increases, so might the risk of offering therapy to clients who are not optimally disposed to engage with and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
4
11
1
1
Order By: Relevance
“…The current study provides initial evidence that individually tailored yet manualized CBT can effectively treat distressing voice‐hearing experiences occurring across diagnoses within routine clinical practice. With regards to the first question, we replicated the previous finding from the Sussex Voices Clinic (Hayward, Edgecumbe, et al, ; Paulik et al, ) that brief CSE (the B in CBT) leads to significant yet modest improvements in voice‐related distress, with just under half the sample (41.9%) reporting clinically meaningful improvements. The effect sizes reported in the current study were larger than those reported by Hayward et al (2017).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The current study provides initial evidence that individually tailored yet manualized CBT can effectively treat distressing voice‐hearing experiences occurring across diagnoses within routine clinical practice. With regards to the first question, we replicated the previous finding from the Sussex Voices Clinic (Hayward, Edgecumbe, et al, ; Paulik et al, ) that brief CSE (the B in CBT) leads to significant yet modest improvements in voice‐related distress, with just under half the sample (41.9%) reporting clinically meaningful improvements. The effect sizes reported in the current study were larger than those reported by Hayward et al (2017).…”
Section: Discussionsupporting
confidence: 83%
“…The demographic and clinical characteristics of the 62 clients included in this study are reported in Table . Client characteristics of the study sample are comparable with other studies of CBT in similar voices clinics (Paulik et al, ; Thomas, Rossell, Farhall, Shawyer, & Castle, ).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Two trials of CSE with people diagnosed with schizophrenia found reduced symptom severity compared with both treatment-as-usual and supportive counselling (Tarrier et al, 1993, Tarrier et al, 1998). A brief four-session format specifically targeting voices appears feasible, and has been associated with reduced hallucination-related distress post-treatment (Hayward et al, 2018; Paulik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Those who seek help for hallucinations often choose to reduce the level of distress elicited by these perceptions as their main goal for recovery (Greenwood et al, 2010), rather than to eliminate the experience altogether. Drawing on this evidence, there has been considerable investment in developing symptom-focused psychological services ("voices clinics"; Paulik, Thomas, Glasshouse, & Hayward, 2019) and treatments selectively targeting distressing hallucinations (e.g., Fielding-Smith et al, 2015;Hayward, Edgecumbe, Jones, Berry, & Strauss, Hazell, Hayward, Cavanagh, Jones, & Strauss, 2018;Louise, Rossell, & Thomas, 2019;Paulik, Jones, & Hayward, 2018). Furthermore, evidence from self-help groups and cognitive behaviour therapy for psychosis indicates that as distress from hallucinations begins to decline, clients often report that they are feeling better in daily life (Lincoln, Jung, Wiesjahn, & Schlier, 2016;Longden, Read, & Dillon, 2018), which suggests that treatment for hearing voices may have a broader benefit to emotional functioning.…”
Section: Introductionmentioning
confidence: 99%